Natural plant extracts as active components in chitosan-based films: A comparative study. (September 2019) - Bajić, Marijan; Ročnik, Tina; Oberlintner, Ana; Scognamiglio, Francesca; Novak, Uroš; Likozar, Blaž
Graphical abstract: Highlights: Oak and hop extracts-containing films exhibited the best properties. Oak and hop extracts incorporation allowed light blockage at the wavelengths below ∼330 nm. Oak and hop extracts endowed films by antimicrobial activity against Bacillus subtilis . The highest total phenolic content was in the oak extract-containing film. Abstract: Chitosan-based films with separately incorporated plant extracts obtained from oak ( Quercus robur ), hop ( Humulus lupulus ), and brown algae ( Laminaria hyperborea ) were evaluated and mutually compared regarding structural, physicochemical, and antibacterial properties. Processing of chitosan and extracted raw substances led to the development of blended films with diverse physical appearances and physicochemical properties. Starting from the oak extract-containing film and ending with the algal extract-containing film, blended films shown ascending trends in moisture content (21.5% – 28.3%), total soluble matter (23.8% – 28.9%), and elongation at break (14.0% – 31.0%) as well as descending trends in tensile strength (12.7 MPa – 5.5 MPa), Young's modulus (230.8 MPa – 19.4 MPa), and total phenolic content (9.1 mgGAE gfilm −1 – 1.0 mgGAE gfilm −1 ). The films loaded with oak and hop extracts had improved optical properties reflected in the ability to completely block the light transmittance at the wavelengths below ∼330 nm. Moreover, the same films exhibited the appearance of inhibition zones implying the antibacterial activity against Bacillus subtilis .